(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The text proposes a new visit the literary inquisition and theatrical censorship in the 16th century in Portugal, a time when pomp and culture, provided by the huge profits of colonialism, which granted Lisbon court the presence of Gil Vicente (c.1465- c.1536): goldsmith, playwright, director and artist, he wrote, from 1502 to 1536, about 45 plays, some of them made silent by the machinery of the Holy Office Court, established in 1536. This paper was carried out to delineate, mainly, a historical moment which put an end to Gil Vicente’s work: In Brussels (Flandres), on December 21, 1531, a short play by Gil Vicente, Jubileu de Amores, to celebrate the birth of D. Manuel, son of the King D. João III. Among the people in the audience there was Girolano Aleandro, a diplomat sent by the Pope to persuade the Emperor Charles V to intervene against the German heresy, aroused by Martin Luther. In a letter sent to the Pope’s secretary, Aleandro wrote a severe criticism against Gil Vicente’s comedy, in which there was a recrimination of the system of indulgences granted by Rome. The play was staged in the Portuguese court nor was included into Copilaçam deTodalas obras de Gil Vicente of 1562 and disappeared without trace.